Pengembangan Modul Biologi Berbantuan Qr-Code Untuk Memfasilitasi Gaya Belajar Siswa SMA Pada Materi Inovasi Teknologi Biologi - Rahmatika Febrianty; Mariani Natalina; Darmadi Darmadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to produce a Biology Module assisted by QR-Code to facilitate the learning styles of high school students on quality Biological Technology Innovation. This type of research is research and development that uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), limited to the third stage (development). The instruments used in this research are validation sheets and response questionnaires. The assessment was conducted by two expert lecturers by filling out the validation sheet and two high school biology teachers. The overall validation results of the QR-Code assisted Biology Module achieved an average score of 3.89, classified as very valid. The QR-Code assisted Biology Module was tested on seventh semester students of the Biology Education Program at Riau University in a limited trial stage 1, achieving an average score of 3.78 which falls into the very good category. Subsequently, the QR-Code assisted Biology Module was tested on tenth grade students at Cendana High School in Pekanbaru during the limited trial stage 2, achieving an average score of 3.83, also in the very good category. Based on the average scores from the validation and limited trial tests of stages 1 and 2, it can be concluded that the QR-Code assisted Biology module meets the criteria of being very valid and very good as a teaching module, with a score of 3.83.